Prevalence of group B streptococcus anogenital colonization and feasibility of an intrapartum screening and antibiotic prophylaxis protocol in Cameroon, Africa. Issue 2 (10th June 2019) - Subramaniam, Akila; Blanchard, Christina T.; Ngek, Ekongefeyin S.N.; Mbah, Rahel; Welty, Edith; Welty, Thomas; Dionne‐Odom, Jodie; Sander, Melissa; Halle‐Ekane, Gregory; Tita, Alan T.N.
Abstract: Objective: To evaluate group B streptococcus (GBS) colonization prevalence and feasibility of intrapartum GBS screening/antibiotic prophylaxis (IAP) in Cameroon, Africa. Methods: Prospective cohort in the Cameroon Baptist Convention Health Services network. Maternity providers collected anogenital swabs from consenting term women in labor for testing by a rapid GBS‐polymerase chain reaction (PCR) system. Positive tests (GBS+) resulted in initiation of intravenous ampicillin until delivery. Primary outcomes were GBS prevalence and proportion of GBS+ women receiving ampicillin before delivery and more than 4 hours before delivery. Results: A total of 219 women were enrolled from January 10 to April 27, 2017. GBS prevalence was 12.3% (95% confidence interval [CI] 7.9–16.7) with GBS+ women more likely to reside in urban areas (19.6% vs 9.7%, P =0.004). Of 27 GBS+ women, 19 (70.4%) received ampicillin before delivery and 14 (51.9%) 4 hours or longer before delivery. A median two doses of ampicillin (interquartile range [IQR] 1–5) were given and started at a median of 105 minutes (IQR 90–155) after swab collection and 20 minutes (IQR 10–45) after GBS result. Of the 8 women who did not receive ampicillin, 7 (87.5%) delivered before test results. Conclusion: A GBS IAP protocol is feasible in Cameroon and should be evaluated for widespread implementation in Cameroon and other low‐income countries to decrease GBS‐related morbidity. Abstract : A polymerase chain reaction‐based rapid group B streptococcus screening and intrapartum antibiotic prophylaxis protocol is both feasible and acceptable to obstetric providers in the low‐income country of Cameroon, Africa.